Boundedness of Parametrized Littlewood-Paley Operators with Variable Kernels on weighted Morrey Spaces - Xin, Yinping; Wang, Shanlin; Chen, Xiaohua; Liu, Shuo (Journal of Informatics and Mathematical Sciences, 2017)
In this paper,we establish the boundedness of parameterized area integral \(μ_{Ω,S}^{ρ}\) and the Littlewood-Paley \(g_{λ}^{*}\) function \(μ_{Ω,λ}^{*,ρ}\) with variable kernel on weighted Morrey space \(L^{p,k}(ω)\).